METHODOLOGICAL ASPECTS OF TEACHING REGIONAL SCIENCE AT LINGUISTICS UNIVERSITY, NIZHNY NOVGOROD - Maria Samoilova (Сравнительная политика, 2015)
The appearance of Regions Science as an academic discipline is connected to the development of regional science as a scientific field. As a field of social science regional science is still on its way of becoming mature: it is yet to introduce its specific scientific method. At present even the very principles of world regional division are subject of a debate. It is this character of uncertainty that regional science has at this stage of development that poses most problems for teachers.